DAMPAK TRANSISI UANG TUNAI KE UANG DIGITAL TERHADAP INKLUSI KEUANGAN DI INDONESIA PERSPEKTIF EKONOMI SYARIAH - Siti Maisaroh; Sri Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2024)
Financial inclusion is crucial for Indonesia's economic development, yet significant challenges remain in serving underserved groups such as rural communities, MSMEs, and low-income households. This study aims to analyze the transition from cash to digital money and its implications for financial inclusion in Indonesia from an Islamic economic perspective. The research focuses on the interplay between digital financial technology adoption particularly e-wallets and QRIS and adherence to Islamic financial principles, including prohibitions on riba (usury), gharar (uncertainty), and unfair transactions.Using a qualitative approach, the study employs literature reviews, case analyses, and in-depth interviews with stakeholders, including digital payment users, Islamic finance experts, and regulators. Data triangulation ensures comprehensive insights. Results indicate that while digital money facilitates financial inclusion by increasing accessibility, literacy, and convenience, concerns over shariah compliance hinder adoption among conservative Muslim users. Notably, awareness and education about Islamic principles in digital finance positively influence acceptance.This research highlights the importance of integrating Islamic values into digital financial services to enhance trust and participation. Policymakers and financial institutions should prioritize shariah-compliant innovations and targeted educational campaigns to address barriers. These findings contribute to advancing inclusive financial ecosystems that align with the socio-religious context of Indonesia.